Given that f(x) = x^2 (3x - 1)^(1/2) find f'(x)

This is an example of a question using the product rulelet u = x2 and v = (3x - 1)1/2then u' = 2x and v' = 3 X 1/2 (3x - 1)-1/2 using the product rule we get f'(x) = x2 X 3/2 (3x - 1)-1/2 + (3x - 1)1/2 X 2xwhich is simplified to = x(15x - 4) / [2(3x - 1)1/2]

Related Maths A Level answers

All answers ▸

Integrate sin(x)cos(x)^2 from 0 to π/2


2x + y = 12. P = xy^2. Show that P = 4x^3 - 48x^2 + 144x


What is the difference between a definite integral and an indefinite integral?


A curve has the equation y = 2x cos(3x) + (3x^2-4) sin(3x). Find the derivative in the form (mx^2 + n) cos(3x)


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences